Organizational Communication Between Commanders and Members at Mabes TNI Kogartap III Surabaya During The Covid-19 Pandemic - Elvitarani, Ovi Ayunda; Rachma Dewi, Putri Aisyiyah (The Commercium, 2023)
This research has a background from the existence of an organizational communication process during the Covid-19 pandemic which took place within the TNI Headquarters Kogartap III organization in Surabaya, which involved commanders and members of TNI soldiers. The purpose of this study was to find out how organizational communication and organizational communication barriers were in Kogartap III Surabaya during the Covid-19 pandemic. The theories used are the classical management theory by Henri Fayol and organizational communication barriers. Based on the research results, there are 5 elements of management that are used based on Henri Fayol's classical management theory. The first is planning by forming continuous, tentative, and incidental work programs. The second is organizing, with an organizational structure based on a hierarchy and vertical flow. Third, namely commanding, that the head of the work unit has the authority and responsibility for the implementation of management activities. Fourth, namely coordinating, coordination is carried out on tasks so that they are in accordance with the main tasks and functions. Fifth, namely controlling, monitoring and evaluating work programs during the Covid-19 pandemic. In the process of organizational communication during the Covid-19 pandemic, Kogartap III relied on technological media such as WhatsApp, Zoom, and the Kogartap E-Office to carry out communication and coordination in assignments. The obstacles found in it include ecological obstacles due to restrictions during the Covid-19 pandemic and technical obstacles due to the difficulty of internet networks and organizational members having difficulties using the latest technological media.Keywords : Organizational Communication, Theory of Henri Fayol, Kogartap III Surabaya